An assessment of fluoride related posts on Instagram - Corey H. Basch; Nicole Milano; Grace C. Hillyer (Tabriz University of Medical Sciences, 2019)
Background: Social media is a driving force in the sharing of information. The purpose of this study is to describe fluoride related content on Instagram, a popular social media platform. Methods: Content categories were created and coded to better describe the nature of the posts.Data collection occurred in three sessions, two months apart. Only relevant posts that included images and had text written in the English language were included. Results: The most common topics were conspiracy theory, contained in 37.3% of posts, followed by dangers of fluoride to health (30.3%) and benefits of fluoride to teeth (28.7%). Of the posts reviewed, 96/300 (32.0%) contained pro-fluoride content while 139/300 (63.0%) posts featured anti-fluoride content. Content varied significantly between pro- and anti-fluoride posts.Conclusion: Our review of Instagram posts revealed that there were approximately 300 posts focused on fluoride related content. Of these posts, there was a higher number of anti-fluoride related content compared to pro-fluoride related content. With accessibility comes the potential for misinformation. Future efforts from medical providers need to focus on educating consumers about reliable sources for health information on the internet.